Pengaruh Pengetahuan Produk dan Gratis Ongkir Terhadap Keputusan Pembelian dengan Variabel Moderasi Potongan Harga Pada Pelanggan Tiktok Shop (Studi Pada Mahasiswa ITBK Bukit Pengharapan) - Karolin, Angela; Djong, Alexander Mario Retto (Universitas Muria Kudus, 2025)
This research was conducted on TikTok Shop customers using a quantitative method. The purpose of this study is to examine and analyze the influence of product knowledge and free shipping on purchasing decisions, with price discounts as a moderating variable. The study's population and sample consist of 100 students from ITBK Bukit Pengharapan. Purposive sampling technique. Data collection was carried out through the distribution of questionnaires. Data analysis in this study used SPSS version 27 and Microsoft Excel. The data analysis methods used were instrument testing, classical assumption testing, and hypothesis testing. The results of the research analysis show that product knowledge, free shipping, and price discounts have a positive and significant partial and simultaneous effect on the purchase decisions of ITBK Bukit Pengharapan students on TikTok Shop. The interaction between product knowledge and price discounts has a positive and significant effect on purchase decisions. The interaction between free shipping and price discounts has a positive and significant effect on purchase decisions. This means the discount variable is able to moderate and strengthen the influence of the independent variable on the dependent variable.